2016
DOI: 10.1155/2016/4692424
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic and Safety Evaluation of Combined Aqueous Extracts ofAzadirachta indicaandKhaya senegalensisin Chickens Experimentally Infected withEimeriaOocysts

Abstract: Coccidiosis is a disease of economic importance in poultry causing morbidity and mortality. Reports show that Azadirachta indica and Khaya senegalensis have been used individually in the treatment of avian coccidiosis. We thus investigated the efficacy and safety of the combined aqueous extracts of these plants for the treatment of experimentally induced coccidiosis in broiler chickens using oocyst count, oxidative stress biomarkers, serum biochemistry, histology, and haematological parameters. The phytochemic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
16
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(22 citation statements)
references
References 20 publications
5
16
0
1
Order By: Relevance
“…The present study showed that Eimeria species lead to the degenerative changes in the positive control group while garlic supplementation decreased the intestinal lesion. Findings of the present study supported the findings of Gotep et al (2016) who reported the highest capacity of crypt and villi of small intestines by the addition of garlic in the broilers feed infected with coccidiosis. The results obtained in groups treated with amprolium and garlic powders may be due to the presence of the chemical hydrochloride in amprolium hydrochloride and allicin and phenolic compounds in garlic, which alter the cytoplasmic penetrability and finally damage the Eimeria cells.…”
Section: Discussionsupporting
confidence: 92%
“…The present study showed that Eimeria species lead to the degenerative changes in the positive control group while garlic supplementation decreased the intestinal lesion. Findings of the present study supported the findings of Gotep et al (2016) who reported the highest capacity of crypt and villi of small intestines by the addition of garlic in the broilers feed infected with coccidiosis. The results obtained in groups treated with amprolium and garlic powders may be due to the presence of the chemical hydrochloride in amprolium hydrochloride and allicin and phenolic compounds in garlic, which alter the cytoplasmic penetrability and finally damage the Eimeria cells.…”
Section: Discussionsupporting
confidence: 92%
“…The best growth performance and parasitological results were observed in Eimeria tenella infected chicks, treated with herb extracts with higher body weight gain, lower feed conversion ratio, light post mortem ceacal lesions, lower proportion of bloody droppings and significant fewer oocysts excretion, comparable to the conventional anticoccidian Vol.42 (2): 7269-7278. https://doi.org/10.35759/JAnmPlSci.v42-2.8 effect. The beneficial effect of medicinal plants in the control of avian coccidiosis was observed by several authors (Gotep et al, 2016;Dakpogan et al, 2018). The herein results agreed with many other findings about the effectiveness of herb extracts utilization against chicken coccidiosis.…”
Section: Discussionsupporting
confidence: 91%
“…A large number of research reports have shown that botanicals and their antioxidant compounds have excellent anticoccidial potential and proven to be best alternative to synthetic anticoccidial drugs Alzahrani et al, 2016;Fall et al, 2016;Gotep et al, 2016). Plants, rich in antioxidant compounds, have also shown remarkable immunomodulatory effects (Abbas et al, 2017a & b).…”
Section: Discussionmentioning
confidence: 99%